Domestic versus Cross-Border Acquisitions: Which Impact on the Target Frims' Performance? - Olivier Bertrand; Habib Zitouna (The Research Institute of Industrial Economics (IUI), 2005)
This paper investigates the effects of horizontal acquisitions on the performance of target firms in the 1990's. Using French manufacturing firm-level data, we examine two main indicators of performance: the profit and the productive efficieny. We distinguish domestic from cross-in-difference estimation techniques associated to a matching propensity score procedure. We find that M&A do not increase the profit of French target firms. These results suggest that firms probably redistribute efficiency gains at the upstream and/or downstream production stage. There is no evidence of an increase in market power. In addition, the consequences of domestic and cross-border M&A significantly differ. Efficiency gains are stronger for cross-border M&A. This conclusion is however true only for extra-Europan Union operations. The achievement in the European economic integrtion certainly explains the absence of difference between European and domestic acquisitions. Finally, our results cast some doubt on the frequent discrimination attitude towards foreign takeovers and the fears of their impact on firms' performance and the hos country's welfare.
Keywords: F23; L10; L20; 330; Multinational Firms; Foreign Direct Investment; Mergers and Acquisitions; Take-Overs; Firms' Performance; Multinationales Unternehmen; Direktinvestition; Übernahme; Fusion; Unternehmenserfolg; Frankreich